The Socialist Party facing the challenges of nation building in Senegal : analysis of the political discourse of the colonial and postcolonial period - (:unkn) unknown (My University, 2021)
Nation-building, one of the major challenges for most political leaders in African countries in the pre- and post-independence period, has not been an easy task, both in practice and symbolically. Indeed, the very first challenge was to forge a unique identity corresponding to the aspirations of their people. But, after independence, this project faces enormous difficulties to materialize.Moreover, the word nation, despite its recent use in reference to the philological study by Marcel Mauss (Mauss, 2013), undoubtedly reveals among African politicians of the postcolonial period their common desire to embark on a path unification of their peoples beyond their specificities and their cultural diversity. But, from a symbolic point of view, specific to the politicians of French West Africa, this concept of nation does not correspond to the African reality, because it embodies a whole imaginary which sometimes goes beyond the national framework stricto-sensu. Returning to the issues of national construction, both material and imaginary, which the Socialist Party faced during the colonial and postcolonial period, is therefore the aim of this research.Through a textometric analysis of the political discourse of two illustrious speakers and main leaders of the Senegalese Socialist Party: L. S. Senghor and Abdou Diouf, this thesis seeks to track down traces of this African identity steeped in foreign identities. Hence a cultural heritage that seems to seal the fate of the peoples of West Africa in general and Senegal in particular. This thesis therefore remains a means for us to question the survival of the African tradition in Senegalese political discourse, more particularly of the Socialist Party, craftsman of independence and whose history coincides with that of Senegal in many respects.
Keywords: African Research